The Museum of Women of Montenegro – An Encounter of Digital Humanities and Cultural Feminism (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The aim of this paper is twofold. Firstly, to present the digital Museum of Women of Montenegro and the ways in which this initiative challenges the boundaries between public and private history by collecting and classifying data on the cultural, social, scientific and political work of women in Montenegro, mostly in the 20th century. Furthermore, the paper aims to contextualize this digital museum in relation to the development of feminist theory in the second half of the 20th century – i.e. in relation to radical and cultural feminism. Finally, the paper will discuss how the encounter of digital humanities as a method of study and the feminist perspective on history contributes to contemporary tendencies in (re)writing women’s history, that is, how local initiatives such as the Museum of Women of Montenegro fit into global trends in women’s studies.
Keywords: Museum of Women of Montenegro; digital humanities; cultural feminism; women’s history; women’s studies